ISOLASI CENDAWAN ENDOFIT DARI AKAR WANGI (Vetiveria zizanioides L.) DAN POTENSINYA SEBAGAI ANTIMIKROBA - Harahap, Israwati; Elsie, - (Sistem Informasi, 2017)
Endophytic fungi are microorganisms living in healthy tissue of their host plants without causing disease. Endophytic fungi live in every plant, including Vetiveria zizanioides L. medicinal plant intracellulary and/or intercellulary. This plant was screened pharmacologically for antibacterial, antifungal, anticataleptic, analgesic and anti-inflammatory, rheumatism, anti oxidant and anti arthritic activity. This research aimed to isolation endophytic fungi from V. zizanioides L. and to screening their antimicrobial potency against microflora Escherichia coli, Staphylococcus aureus, and Candida albicans. Endophytic fungi isolation from V. zizanioides L. was done by surface sterilization method. A total of 33 isolates were recovered from 88 leaves and 88 root segments. Based on antimicrobial activitytest, most of the fungal extracts showed in vitro inhibition of microbes growth.